Planting exotic relatives has increased the threat posed by Dothistroma septosporum to the Caledonian pine populations of Scotland. (10th November 2017) - Piotrowska, Marta J.; Riddell, Carolyn; Hoebe, Peter N.; Ennos, Richard A.
Abstract: To manage emerging forest diseases and prevent their occurrence in the future, it is essential to determine the origin(s) of the pathogens involved and identify the management practices that have ultimately caused disease problems. One such practice is the widespread planting of exotic tree species within the range of related native taxa. This can lead to emerging forest disease both by facilitating introduction of exotic pathogens and by providing susceptible hosts on which epidemics of native pathogens can develop. We used microsatellite markers to determine the origins of the pathogen Dothistroma septosporum responsible for the current outbreak of Dothistroma needle blight (DNB) on native Caledonian Scots pine ( Pinus sylvestris ) populations in Scotland and evaluated the role played by widespread planting of two exotic pine species in the development of the disease outbreak. We distinguished three races of D. septosporum in Scotland, one of low genetic diversity associated with introduced lodgepole pine ( Pinus contorta ), one of high diversity probably derived from the DNB epidemic on introduced Corsican pine ( Pinus nigra subsp. laricio ) in England and a third of intermediate diversity apparently endemic on Caledonian Scots pine. These races differed for both growth rate and exudate production in culture. Planting of exotic pine stands in the UK appears to have facilitated the introduction of two exotic races of D. septosporum into Scotland which now pose a threat to native Caledonian pines both directly and through potential hybridization and introgression with the endemic race. Our results indicate that both removal of exotic species from the vicinity of Caledonian pine populations and restriction of movement of planting material are required to minimize the impact of the current DNB outbreak. They also demonstrate that planting exotic species that are related to native species reduces rather than enhances the resilience of forests to pathogens.